Pengaruh Kualitas Produk, Kualitas Pelayanan, Dan Harga Terhadap Kepuasan Pelanggan Roti Bakar - Fajar Saputro; Muhammad Jalari (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research was conducted to examine how quality, product, service, and price affect customer satisfaction at Roti Bakar. To collect data for this study, respondents, especially those who had bought toast from Benntak, filled out a questionnaire. By using a purposive sampling technique using the Hair formula, et al., a sample of 100 respondents was obtained for this study. Validity test, reliability test, traditional assumption test, and hypothesis testing are the analytical techniques used in this study. The internet, old research papers, and books on customer satisfaction are where secondary data can be found. The results showed that there was a simultaneous significant effect (Test F) between product quality, service quality, and price. Customer satisfaction is significantly influenced by price, service quality, and product quality, at least partially (t test). The output data processing results show a coefficient of determination (R2) of 0.638, meaning that the effect of product quality, service quality, and price on customer satisfaction can reach 63.8%, with other variables not examined in this study. accounting studies for the remaining 36.2%.